Personal protective equipment training & lived experience for healthcare staff during COVID-19 - Cahill, Joan; Kay, Alison; Howard, Vivienne (My University, 2022)
Objectives: To describe the lived experience of healthcare staff during the Coronavirus Disease 2019 (COVID-19) pandemic relating to the use of personal protective equipment (PPE) and investigate risks associated with PPE use, error mitigation and acceptability of mindfulness incorporation into PPE practice. Methods: A qualitative human factors' study at two Irish hospitals occurred in late 2020. Data was collected by semi-structured interview and included role description, pre-COVID-19 PPE experience, the impact of COVID-19 on lived experience, risks associated with PPE use, contributory factors to errors, error mitigation strategies and acceptability of incorporating mindfulness into PPE practice. Results: Of 45 participants, 23 of whom were nursing staff (51%), 34 (76%) had previously worn PPE and 25 (56%) used a buddy system. COVID-19 lived experience impacted most on social life/home-work interface (n=36, 80%). Nineteen staff (42%) described mental health impacts. The most cited risk concerned 'knowledge of procedures' (n=18, 40%). Contributory factors to PPE errors included time (n=15, 43%) and staffing pressures (n=10, 29%). Mitigation interventions included training/education (n=12, 40%). The majority (n=35, 78%) supported mindfulness integration into PPE practice. Conclusions: PPE training should address healthcare staff lived experiences and consider incorporation of mindfulness and key organisational factors contributing to safety.
Keywords: COVID-19; Healthcare staff; Human factors; Lived experience; Personal Protective Equipment; Immunology, Inflammation & Infection; PPE; WELL-BEING; Work Related Stress; health and safety